"Who maltreats? Distinct pathways of intergenerational (dis)continuity of child maltreatment". (August 2021) - McKenzie, Emma F.; Thompson, Carleen M.; Hurren, Emily; Tzoumakis, Stacy; Stewart, Anna
Abstract: Background: Maltreatment victimization history is an established risk factor for child maltreatment across generations. However, many parents with a victimization history do not maltreat, and many parents with no victimization history do have victimized children. Objectives: To understand differences in demographic and maltreatment risk factors across the following intergenerational patterns of maltreatment: cycle maintainers, cycle breakers, cycle initiators, and a comparison group (no maltreatment). Participants and setting: Data were drawn from a large population-based cohort in Queensland, Australia and included 32, 574 biological parents and their children. Maltreatment experiences as a victim or person responsible for harm towards a child were obtained from the Queensland Child Protection System. Methods: Multinomial regression was completed with the full sample to compare the three maltreatment groups with the comparison group. Logistic regressions were conducted on all pairwise combinations of maltreatment groups. Models accounted for several demographic and maltreatment factors. Results: Compared with breakers, maintainers were more likely to be Indigenous (OR = 1.86), never married (OR = 0.34), younger at first birth (OR = 0.87), have ≥3 children (OR = 1.99), be younger at first—and older at last—maltreatment victimization (ORs = 0.97 and 1.07, respectively), and experience a higher frequency of victimization (OR = 1.05). Amongst maltreaters, males were significantly more likely to be initiators while females were more likely to be maintainers (OR = .62). There were few other differences between initiators and maintainers. Conclusions: Meaningful differences among the three maltreatment groups were revealed suggesting that research should focus on the intergenerational discontinuity of maltreatment.